The problem with transferrin saturation as an indicator of iron 'sufficiency' in chronic kidney disease. Issue 8 (17th April 2020) - Besarab, Anatole; Drueke, Tilman B
Abstract: After a brief review of physiological iron metabolism, we describe diagnostic tests for iron status and iron deficiency anemia in patients without chronic kidney disease (CKD) or inflammation. Thereafter we review the dysregulation of iron metabolism in CKD. Specific emphasis is placed on the role of the 'inflammatory' state that develops with the progression of CKD. It invokes changes in iron metabolism that are the exact opposite of those occurring during pure iron deficiency. As a result, transferrin saturation (TSAT) becomes a poorer index of iron availability to the bone marrow and serum ferritin no longer represents iron that can be used during erythropoiesis. We argue that serum iron may provide more information to guide iron therapy than TSAT. In other words, the emphasis on TSAT is misplaced. With the development of a number of hypoxia-inducible factor prolyl hydroxylase inhibitors, which restore iron metabolism toward the 'physiologic state', the iron indices indicating sufficient iron availability to avoid functional iron deficiency during therapy of CKD-associated anemia are likely to change. We summarize these changes in the section 'A peek into things to come!', citing the available data.